Klasifikasi Penggunaan Protokol Komunikasi Pada Trafik Jaringan Menggunakan Algoritma K-Nearest Neighbor - Subrata, Komang Kompyang Agus; Widyantara, I Made Oka; Linawati, Linawati (Majalah Ilmiah Teknologi Elektro, 2016)
ABSTRACT — Network traffic internet is data communication in a network characterized by a set of statistical flow with the application of a structured pattern. Structured pattern in question is the information from the packet header data. Proper classification to an Internet traffic is very important to do, especially in terms of the design of the network architecture, network management and network security. The analysis of computer network traffic is one way to know the use of the computer network communication protocol, so it can be the basis for determining the priority of Quality of Service (QoS). QoS is the basis for giving priority to analyzing the network traffic data. In this study the classification of the data capture network traffic that though the use of K-Neaerest Neighbor algorithm (K-NN). Tools used to capture network traffic that wireshark application. From the observation of the dataset and the network traffic through the calculation process using K-NN algorithm obtained a result that the value generated by the K-NN classification has a very high level of accuracy. This is evidenced by the results of calculations which reached 99.14%, ie by calculating k = 3.
Keywords: Network protocol, K-NN, QoS, network capture